PEMODELAN TRAFIK DAN PENGENDALIAN UMPAN-BALIK JARINGAN JALAN KERETA-API - Danus, Muhar
Abstract: Railway traffic is a set of trains moving consecutively on a railway traffic, passing through consecutive stations. Every train must stop to pick up and drop off passengers at every station. Railway traffic are knows to be unstable, meaning there is a time lag/delay against the trains original schedule. Therefore traffic control is needed to avoid instability and disturbances on railway operation. The system dynamics are defined as state variables and it is given a linear feedback control with a minimum quadratic performance index in order to stabilize the system. The methode which will be implemented is discrete-event based which takes into account discrete-events that can occur on railway traffic. These events are known as timed-discrete events because each event is dependent on time. Robustness of the control systems to disturbances will also be demonstrated with computer simulation. The simulation show that by using the u-control law the performance index can be controlled.